Abū al-Barakāt al-Baghdādī as a precedent to Ibn Taymiyya on Allāh's perfection and perpetual activity - Hussain, Issarar (2024)
This thesis is a comparative study of the theology of Abū al-Barakāt al-Baghdādī and Ibn Taymiyya. Ibn Taymiyya's theology is unique in Sunni Islam as it is distinct from the dominant Asharism of the Kalām theologians and the non-cognitivism of the Hanbalites. There are many predecessors who Ibn Taymiyya read and appropriated in order to develop his unique views and Abū al-Barakāt is one who he quotes in many of his works; yet the relationship between the ideas of both has not previously been explored. This dissertation will demonstrate how Abū al-Barakāt is a striking precedent to Ibn Taymiyya in various elements of his theology. Chapter One discusses Allāh's perfection according to both. Chapter Two discusses Allāh's will and perpetual activity according to both, which is how both characterise Allāh's perfection. Chapter Three discusses the understanding of time in relation to Allāh according to both as it is necessary to understand the relationship between time and Allāh according to both in order to fully understand the nature of Allāh's perpetual activity.